Intravenous opioid drug abuse as an independent risk factor for supraglottic squamous cell carcinoma—A case‐control study. (9th October 2017) - Shoffel‐Havakuk, H.; Cohen, O.; Slavin, M.; Haimovich, Y.; Halperin, D.; Lahav, Y.
Abstract : Objectives: Intravenous opioid drug abuse (IVDA) was previously correlated with laryngeal cancer. However, discrimination of this correlation by anatomical subsites has not yet been described. In this study, we aim to further establish the association between IVDA and laryngeal squamous cell carcinoma (SCC) and to indicate the laryngeal subsites that are predisposed for this correlation. Design: A retrospective matched case‐control study. Setting and participants: Patients diagnosed with supraglottic SCC (SG‐SCC) between 1996 and 2016 treated in a tertiary academic referral centre were enrolled to the case group. The control group comprised of matched patients diagnosed with glottis SCC (G‐SCC). Matching was based on gender, age and socio‐economic rank. Main outcome measures: Variables studies as risk factors included the following: smoking, alcohol consumption, history of IVDA and infectious diseases. The variables were tested for association with the 2 groups and with each other. Results: Forty‐eight patients with SG‐SCC were matched with 48 patients with G‐SCC. IVDA rates significantly increased among patients with SG‐SCC. Of the SG‐SCC group, 18.8% had a positive history for IVDA compared with 2.1% of the G‐SCC ( P  = .008). A history of IVDA was found to be a risk factor for SG‐SCC, independent of smoking, excessive alcohol and socio‐economic status. The odds ratio for patients with an IVDA history to have SG‐SCC relatively to G‐SCC was 10.846 (95% CI: 1.3‐89.4). Conclusions: Intravenous opioid drug abuse represents an independent risk factor for SG‐SCC. The pathogenesis should be investigated not just as a risk factor, as opioids are commonly used for pain management in oncologic patients.